Bleeding risk in hospitalized patients with COVID‐19 receiving intermediate‐ or therapeutic doses of thromboprophylaxis. (20th June 2021) - Demelo‐Rodriguez, Pablo; Farfán‐Sedano, Ana Isabel; Pedrajas, José María; Llamas, Pilar; Sigüenza, Patricia; Jaras, María Jesús; Quintana‐Diaz, Manuel; Fernández‐Capitán, Carmen; Bikdeli, Behnood; Jiménez, David; Monreal, Manuel; ,
Abstract: Introduction: Some local protocols suggest using intermediate or therapeutic doses of anticoagulants for thromboprophylaxis in hospitalized patients with coronavirus disease 2019 (COVID‐19). However, the incidence of bleeding, predictors of major bleeding, or the association between bleeding and mortality remain largely unknown. Methods: We performed a cohort study of patients hospitalized for COVID‐19 that received intermediate or therapeutic doses of anticoagulants from March 25 to July 22, 2020, to identify those at increased risk for major bleeding. We used bivariate and multivariable logistic regression to explore the risk factors associated with major bleeding. Results: During the study period, 1965 patients were enrolled. Of them, 1347 (69%) received intermediate‐ and 618 (31%) therapeutic‐dose anticoagulation, with a median duration of 12 days in both groups. During the hospital stay, 112 patients (5.7%) developed major bleeding and 132 (6.7%) had non‐major bleeding. The 30‐day all‐cause mortality rate for major bleeding was 45% (95% confidence interval [CI]: 36%‐54%) and for non‐major bleeding 32% (95% CI: 24%‐40%). Multivariable analysis showed increased risk for in‐hospital major bleeding associated with D‐dimer levels >10 times the upper normal range (hazard ratio [HR], 2.23; 95% CI, 1.38–3.59), ferritin levels >500 ng/ml (HR, 2.01; 95% CI, 1.02–3.95), critical illness (HR, 1.91; 95% CI, 1.14–3.18), and therapeutic‐intensity anticoagulation (HR, 1.43; 95% CI, 1.01–1.97). Conclusions: Among patients hospitalized with COVID‐19 receiving intermediate‐ or therapeutic‐intensity anticoagulation, a major bleeding event occurred in 5.7%. Use of therapeutic‐intensity anticoagulation, critical illness, and elevated D‐dimer or ferritin levels at admission were associated with increased risk for major bleeding.